Correlation studies in watermelon [Citrullus lanatus (Thumb.) Mansf.] (Indian Journal of Arid Horticulture, 2018)
Watermelon [Citrullus lanatus (Thunb.) Mansf.] is package of practices was followed for raising the crop. The  one of the most important cucurbitaceous fruit crop grown in observations on 18 attributes including growth, yield  different parts of Rajasthan as well as in India. It is consumed attributes and quality parameters were recorded on five  as dessert fruit and very often known as thirst quencher. It is randomly selected plants from each replication during both  extensively cultivated both under irrigated and riverbeds. the years. The collected data were averaged and correlation  Watermelon is very low in cholesterol and sodium. It is rich (phenotypic and genotypic) was computed as described by  source of lycopene, a powerful antioxidant. Its 100g edible Singh and Choudhary (1977) and as per formula (Johnson et  portion contains 95.8g moisture, 0.2g protein, 0.2g fat, 0.2g al. 1955).
Keywords: Watermelon; moisture; randomly